Development of approach to enhance thermoelectric performance of two-dimensional materials - Liao, Jia Hui (Nanyang Technological University, 2023)
2D materials have attracted much interest among scientists due to their superior physical and thermoelectric properties. In comparison to their bulk material counterparts, 2D materials display greater flexibility, atomically thin layer structure, and superior thermoelectric properties. These attributes highlight the immense potential of 2D materials in electronics and optoelectronics. In particular, few-layered Bi2O2Se has emerged as a novel 2D material with high carrier mobility and superior air stability. In addition, Bi2O2Se exhibits high thermoelectric performance over a wide temperature range as compared to other 2D materials. However, the low carrier mobility of the material at room temperature caused by strong phonon scattering remains a major obstacle to the improvement of its thermoelectric performance. Therefore, this study aims to design and develop an approach to improve carrier mobility and consequently, improve the thermoelectric performance of 2D materials. This will be achieved with the use of substrates with uneven surfaces, which creates lattice distortion in the 2D material that modifies the dielectric constant and decreases phonon scattering. The measurement data obtained will then be analyzed to validate the effectiveness of the approach in enhancing the thermoelectric performance of 2D materials and improve the understanding of how carrier mobility independently affects the thermoelectric performance of the material.